Analisis Customer Relationship Marketing Terhadap Kepuasan Dalam Meningkatkan Loyalitas Nasabah PT. BNI (Persero) - Sri Wardani; Zulkarnain Zulkarnain; Samsir Samsir (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
The study was conducted at Bank BNI (Persero) Tbk Regional Area Pekanbaru. The aim is to find out the direct effect of the CRM Dimension, namely Trust, Communication, Commitment, Conflict handling, Emphaty on customer satisfaction and loyalty. This study took a sample of 100 consumers. The variables used are Trust, Communication, Commitment, Conflict handling, Emphaty on customer satisfaction and loyalty. Data were analyzed using SEM (Structural Equation Modeling) analysis which is operated through the Smart PLS 3.2.8 program. The results showed that there is an influence of Trust, Communication, Commitment, Conflict handling, Emphaty on customer satisfaction and loyalty. And there is an influence between customer satisfaction variables on customer loyalty, the better the customer satisfaction, the better customer loyalty will be.